Heavy metal contamination status in the soil-water-rice system near coal-fired power plants in Cilacap, Indonesia - Febbyandi Isnanda Pandiangan; Kholis Abdurachim Audah (Universitas Lancang Kuning, 2022)
Indonesia is intensively developing plenty of coal-fired power plants to support electricity demand growth. Some research showed the utilization of coal as an electrical energy source may produce anthropogenic contaminants (ACs) that can bioaccumulate in plants. This research was carried out to investigate the severity of the heavy metals contamination problem, for instance, arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) in soil, water, rice, and rice bran using ICP-MS and ICP-OES. This research demonstrated the metal contamination levels of arsenic, cadmium, mercury, and lead in the soil, water, rice, and rice bran were below the maximum limit, according to SNI, Codex, and FAO/WHO. However, only a rice sample showed the lead (Pb) level above the safe limit. Coal-fired power plant activities in Cilacap did not indicate clear evidence of soil, water, rice, and bran heavy metal contamination. Therefore, transformation to green energy (e.g., solar and geothermal) is highly recommended to minimize the potential health risks of environmental pollution due to the coal-fired power plant's by-product activities.